ByzRev 02.2020.011: Erika Manders – Daniëlle Slootjes (Hgg.), Leadership, Ideology and Crowds in the Roman Empire of the Fourth Century AD: (Heidelberger Althistorische Beiträge und Epigraphische Studien 62). Stuttgart: Franz Steiner Verlag 2020. - Sandberg, Matthias (The Byzantine Review, 2020)
Erika Manders – Daniëlle Slootjes (Hgg.), Leadership, Ideology and Crowds in the Roman Empire of the Fourth Century AD (Heidelberger Althistorische Beiträge und Epigraphische Studien 62). Stuttgart: Franz Steiner Verlag 2020. 200 S. – ISBN 978-3-515-12404-1 (€ 44,–)